Endoscopic submucosal dissection in rectal tumors extending or not to the dentate line: A comparative analysis. Issue 3 (March 2020) - Roland, Déborah; Rahmi, Gabriel; Pérez-Cuadrado-Robles, Enrique; Perrod, Guillaume; Jacques, Jérémie; Barret, Maximilien; Leblanc, Sarah; Berger, Arthur; Albouys, Jérémie; Chaussade, Stanislas; Cellier, Christophe
Abstract: Background: The feasibility of endoscopic submucosal dissection (ESD) in rectal tumors extending to the dentate line (RTDL) is unclear. Aims: To analyze the outcomes of ESD in RTDL compared to non-RTDL, with a special focus on the lower rectum location. Methods: Observational multicenter retrospective study. All patients with a rectal tumor who underwent ESD in 2013–2017 were included. A comparative analysis between RTDL and non-RTDL groups was done. Results: Two-hundred and twenty-eight patients (median age: 69 years, range: 33–89, 51.3% male) with RTDL (n = 65, 28.5%) and non-RTDL lesions (n = 163, 71.5%) were included. There were no significant differences between the en-bloc (89.2% vs. 90.8%, p = 0.718), complete (60% vs. 71.8%, p = 0.084) and curative resection rates (58.5% vs. 68.7%, p = 0.141). The overall complication rate (4.6% vs. 8%, p = 0.370) was not different, independently of the rectal location. Local recurrence was higher in RTDL (7.3% vs. 1.5%, p = 0.065). The indication for surgery due to non-curative resections in the lower rectum was lower in RTDL (9.2% vs. 14.6%, p = 0.378). Conclusion: The safety, effectiveness and long-term impact of ESD in RTDL and non-RTDLs is comparable. Local recurrence in the lower rectum may be higher in RTDL.